The effects of multiple ischemia and survival times on hippocampal CA1 neuronal cell loss in a rat model of global ischemia: A long-term ischemia maturation study. - Todd, Michael. (University of Ottawa (Canada), 1998)
We investigated the effects of varying ischemia and survival times on CA1 neuronal loss. Histological analysis of the hippocampus was performed at 2, 7, 14, 28 and 90 days following 3, 5, 7, 10 and 13 minutes of global forebrain ischemia. Our results indicate that the ischemic maturation process extends beyond 7 days. Ten and thirteen minutes of ischemia produced a significant degree of cell loss by 7 days (70.53% and 83.25% respectively), while average cell death at 90 days survival was approximately 12% higher. Most strikingly, seven minutes of ischemia produced approximately 30% CA1 cell loss at 90 days compared to only 3% cell loss at 7 days, a nine-fold increase. No cell loss was observed at 2 and 7 days survival following 5 minutes of ischemia, but an average of 5.6% cell loss was observed at 3 months. Three minutes of ischemia produced no cell damage. Data collapsed over ischemic severity suggested that there may 2 rates of cell death evident in this study: (1) a rapid cell loss occurring within the first 7 days of ischemia and (2) a slow progressive cell loss occurring over weeks. Ten and thirteen minutes of ischemia possessed the rapid cell death, while 7 minutes appeared to display only slow progressive cell loss. The fact that the ischemic maturation process extends well beyond 7 days and that mild ischemia severities can produce significant cell loss at long survival times holds important implications for drug trials and our current knowledge of death mechanisms. (Abstract shortened by UMI.)
Keywords: Biology, Neuroscience.